Myonuclear Domain Flexibility Challenges Rigid Assumptions on Satellite Cell Contribution to Skeletal Muscle Fiber Hypertrophy - Murach, Kevin A.; Englund, Davis A.; Dupont-Versteegden, Esther E.; McCarthy, John J.; Peterson, Charlotte A. (Frontiers in Physiology, 2018)
Satellite cell-mediated myonuclear accretion is thought to be required for skeletal muscle fiber hypertrophy, and even drive hypertrophy by preceding growth. Recent studies in humans and rodents provide evidence that challenge this axiom. Specifically, Type 2 muscle fibers reliably demonstrate a substantial capacity to hypertrophy in the absence of myonuclear accretion, challenging the notion of a tightly regulated myonuclear domain (i.e. area that each myonucleus transcriptionally governs). In fact, a “myonuclear domain ceiling”, or upper limit of transcriptional output per nucleus to support hypertrophy, has yet to be identified. Independent from fusion, satellite cells play a role in damage repair and remodeling of the extracellular matrix during loading-induced muscle hypertrophy. We postulate that robust satellite cell activation and proliferation in response to mechanical loading is largely for these purposes. Future work will aim to elucidate the mechanisms by which Type 2 fibers can hypertrophy without additional myonuclei, the extent to which Type 1 fibers can grow without myonuclear accretion, and whether a true myonuclear domain ceiling exists.